ANALISIS KUALITAS LAPORAN KEUANGAN PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) SEBELUM DAN SELAMA PANDEMI COVID-19 - Indria Stevani; Dianita Meirini (ITB AAS INDONESIA, 2023)
Abstract This study wants to examine the impact of the COVID-19 pandemic on the quality of financial reports for companies listed on the Indonesia Stock Exchange before and during the COVID-19 pandemic. The independent variable in this study is covid19, while the dependent variable is the quality of financial reports. The research sample consisted of 36 companies listed on the Indonesia Stock Exchange which reported periodically from 2019 to 2020. The data collection method used a purposive sample and this research used secondary data. The research was tested using the SPSS program with the 3-way Anova method and different tests. The results of the study show that the COVID-19 pandemic has a negative effect on the quality of financial reports. This lesson also shows that there are differences in the quality of financial reports before the Covid-19 pandemic and the quality of financial reports after the Covid-19 pandemic. The financial quality of financial reports (2019) has a difference in the quality of financial reports (2020). Keywords: Pandemic Covid19, Quality of Financial Reporting